2016
DOI: 10.1002/ece3.2080
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis indicates that oxidative stress is both a constraint on and a cost of growth

Abstract: Oxidative stress (OS) as a proximate mechanism for life‐history trade‐offs is widespread in the literature. One such resource allocation trade‐off involves growth rate, and theory suggests that OS might act as both a constraint on and a cost of growth, yet studies investigating this have produced conflicting results. Here, we use meta‐analysis to investigate whether increased OS levels impact on growth (OS as a constraint on growth) and whether greater growth rates can increase OS (OS as a cost of growth). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(101 citation statements)
references
References 49 publications
5
94
2
Order By: Relevance
“…Alternatively, the size of an embryo may also reflect its degree of maturation, with larger/more mature embryos showing stronger antioxidant defenses. The observations that embryo size was negatively associated with TOS in the liver and that markers of oxidative status (PC in the liver, TOS and LPO in the brain) negatively predicted brain size are also consistent with expectations, because overproduction of pro-oxidants and the consequent oxidative imbalance should be detrimental to developmental and growth processes (Smith et al, 2016).…”
Section: Questionsupporting
confidence: 83%
“…Alternatively, the size of an embryo may also reflect its degree of maturation, with larger/more mature embryos showing stronger antioxidant defenses. The observations that embryo size was negatively associated with TOS in the liver and that markers of oxidative status (PC in the liver, TOS and LPO in the brain) negatively predicted brain size are also consistent with expectations, because overproduction of pro-oxidants and the consequent oxidative imbalance should be detrimental to developmental and growth processes (Smith et al, 2016).…”
Section: Questionsupporting
confidence: 83%
“…However, importantly, the so far recognised costs of fast growth are primarily manifested not as costs of integral growth rates but rather as costs of high differential growth rates. The latter included lower starvation resistance (Stoks et al 2006, Scharf et al 2009), oxidative stress (De Block and Stoks 2008, Harrison et al 2013, Smith et al 2016, and higher vulnerability of actively foraging larvae to predators (Gotthard 2000, Stoks et al 2005). An explicit attention to DGR is therefore needed in the optimality analyses of growth rate.…”
Section: Discussionmentioning
confidence: 99%
“…These two routes are not mutually exclusive and indeed could act in concert; the increased cell division rate could give rise to increased oxidative stress due to the higher metabolic activity needed to generate more ATP to fuel this growth. A number of correlative and experimental studies have found that relatively fast growth is associated with higher levels of oxidative stress markers in both laboratory and field studies [61,96,97], and a recent meta-analysis has demonstrated that there is good evidence that faster growth incurs increased oxidative damage, and that this may constrain growth strategies [98]. The context in which growth takes place will therefore be expected to influence the level of oxidative stress that occurs.…”
Section: (B) Growth and Telomeresmentioning
confidence: 99%